2014
DOI: 10.1155/2014/140851
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Rate of Insulin Resistance in Patients with Preeclampsia Using HOMA-IR Index and Comparison with Nonpreeclampsia Pregnant Women

Abstract: Women with preeclampsia, independent of obesity and glucose intolerance, exhibit insulin resistance during pregnancy. The purpose of the present study is to determine whether early diagnosis of insulin resistance during pregnancy can predict preeclampsia. Through a case-control study, 675 pregnant women were selected and their first trimester blood was taken. Their fasting blood glucose and insulin were also measured after diagnosis of preeclampsia by 20 weeks of pregnancy. Based on the experiments conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 23 publications
1
23
0
6
Order By: Relevance
“…54 Moreover, coexisting metabolic factors can contribute to endothelial dysfunction, and hyperlipidaemia and insulin resistance have been associated with preeclampsia. [55][56][57] Immune factors, such as auto-antibodies, oxidative stress and natural killer (NK)-cell abnormalities, cause placental dysfunction and impaired placental perfusion. The latter acts as a stimulus of placental release of anti-angiogenic and inflammatory mediators that eventually cause endothelial dysfunction and organ damage.…”
Section: Risk Factorsmentioning
confidence: 99%
“…54 Moreover, coexisting metabolic factors can contribute to endothelial dysfunction, and hyperlipidaemia and insulin resistance have been associated with preeclampsia. [55][56][57] Immune factors, such as auto-antibodies, oxidative stress and natural killer (NK)-cell abnormalities, cause placental dysfunction and impaired placental perfusion. The latter acts as a stimulus of placental release of anti-angiogenic and inflammatory mediators that eventually cause endothelial dysfunction and organ damage.…”
Section: Risk Factorsmentioning
confidence: 99%
“…PE has been recognized as a contributor to maternal mortality and morbidity and affects 3% to 5% of pregnant women worldwide . Beyond the familiar maternal risks such as diabetes mellitus, hypertension, aging, obesity, multiple gestations, and antiphospholipid antibody syndrome, the roles of immunological and genetic factors in PE pathogenesis have also been studied . During pregnancy, the increased susceptibility to oxidative stress (OS) conceivably contributes to indiscriminate damage to biological molecule function when the antioxidant defense cannot bear the reactive O 2 species production .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Beyond the familiar maternal risks such as diabetes mellitus, hypertension, aging, obesity, multiple gestations, and antiphospholipid antibody syndrome, the roles of immunological and genetic factors in PE pathogenesis have also been studied. [4][5][6][7] During pregnancy, the increased susceptibility to oxidative stress (OS) conceivably contributes to indiscriminate damage to biological molecule function when the antioxidant defense cannot bear the reactive O 2 species production. 8,9 Reportedly, pregnancies suffering with PE show disturbance in the pro-oxidant and antioxidant balance, and increased OS as well as the mechanisms of antioxidative defense may be conducive to the process of PE.…”
Section: Introductionmentioning
confidence: 99%
“…Lampinen et al (25) found that early PE may lead to IR disorder. Another study revealed a significant difference in IR state between PE and control groups during the third trimester (26). Practically, all obese women with hypertension have elevated insulin levels (27).…”
Section: Serum Cation Levels In Patient and Control Groupsmentioning
confidence: 99%